Investigation of the Effect of Palmaris Longus Presence on the Upper Extremity and Hand Functions in Individuals of Different Ethnic Origins - Onur Seçgin Nişanci; Rıdvan Yildiz; Sidrenur Aslan Kolukisa (Diagnostics, 2025)
Objectives: This study aims to determine the presence rate of the palmaris longus (PLM) muscle in Turkish and Georgian individuals and to examine its effect on hand/upper extremity function. Methods: The study, conducted at Artvin Çoruh University, included 400 volunteer students (800 hands). The presence of PLM was evaluated with Schaeffer and Thompson tests. Upper extremity and hand functions were measured by the Upper Extremity Function Index (UEFI-15) and the Sollerman Hand Function Test. Data were evaluated with the chi-square test, Mann–Whitney U, and Linear Mixed Model analysis in the SPSS v22 program. Results: PLM muscle was significantly more common in Georgian individuals compared to Turkish individuals (p < 0.05). This difference was statistically significant, particularly in Georgian men (p < 0.05). There was no significant correlation between the presence of PLM and hand and upper extremity functions (p > 0.05). Conclusions: Although the PLM muscle shows different and significant prevalence rates in relation to ethnicity, it does not show a significant effect on hand function. Ethnicity is a determining factor in anatomical and surgical studies of the PLM, and its minimal functional impact on hand function makes its graft use safe.